Big and strong or small and beautiful: Effects of organization size on the performance of farmer cooperatives in China. Issue 1 (12th September 2022) - Liang, Qiao; Bai, Rongrong; Jin, Zhi; Fu, Linlin
Abstract: The relationship between organization size and performance is widely discussed in relation to companies, yet related discussion of farmer cooperatives is limited. This study maps the membership size distribution of farmer cooperatives in China and explores the effects of membership size on the economic performance of cooperatives. A panel dataset of the census of farmer cooperatives in China from 2014 to 2019 is used for the empirical analyses. First, the Pareto indices of farmer cooperatives' size distribution are calculated, and the results feature the dominance of small cooperatives and the underdevelopment of large cooperatives. Second, membership size has a positive effect on the total profit of cooperatives. Third, the impact of membership size on the profit per member displays an inverted "U" pattern, and the optimal membership size is 19 members. These effects are heterogeneous across product categories and cooperative ages. The robustness of the results is confirmed by alternative key explanatory indicators and estimation methods. [EconLit Citations: Q13, L25].